ANALYSIS OF EASY, RISK AND TRUST THAT INFLUENCE ON-LINE SHOPPING DECISIONS - Nuraini, Dewi; Prasetya, Hendra; Herawati, Wiwik (Journal of Industrial Engineering & Management Research, 2022)
The problem discussed in this study is whether convenience, risk and trust partially have a significant influence on online shopping decisions for students in West Surabaya. Thus the aim is to determine the significance of the effect of convenience, risk and trust on online shopping decisions for students in West Surabaya. This type of research is an explanatory research using a quantitative approach. The population is students in West Surabaya. Determination of the sample using purposive sampling technique with a total sample of 110 respondents. The independent variables studied are convenience, risk and trust, while the dependent variable is the purchase decision. Collecting respondent data through the distribution of questionnaires. Data analysis technique using multiple linear regression analysis and hypothesis testing using t test or partial test. The result is that each of the independent variables studied, namely convenience, risk and trust, has a significance value less than 0.05. Thus, the variables of convenience, risk and trust partially have a significant effect on online shopping decisions for students in West Surabaya. We recommend that sellers who sell their products on-line continue to strive to facilitate transactions and increase consumer confidence, while for consumers before deciding to make an on-line purchase, they should seek complete and clear information